Sustainable Consumer Purchasing Behavior as a Result of Kopi Kenangan's Sustainable Business Practices - Muharman, Deddy; Chair , Ahmad Achdan; Arifin , Farah Dewi (Yayasan Ilomata, 2025)
The coffee industry has become one of the sectors receiving increasing attention in the context of sustainability, both from environmental and social perspectives. As awareness grows about the importance of sustainability, consumer purchasing behavior towards coffee brands has also become a primary focus of research. This study builds upon previous research titled